Foramen ovale and associated accessory foramina: A computerized tomography study to determine morphometry and analyze gender and age differences - Eti Sthapak; Navbir Pasricha; Anamika Singh; Rajan Bhatnagar; Ravinder Singh Bedi (Wolters Kluwer Medknow Publications, 2022)
Background: The mandibular nerve exits the cranial cavity by traversing through the foramen ovale (FO) which is located in the greater wing of sphenoid, posterolateral to foramen rotundum. This foramen also provides an entry portal to the accessory middle meningeal artery and helps exit the lesser petrosal nerve apart from the emissary veins. Tumors and masses in infratemporal region require an accurate and precise morphometry of FO, before planning any surgical procedure. The aim of this study is to record and analyze the metric and nonmetric data and compares the morphometry of FO with gender and age. Methodology: Type of study - Retrospective observational study. The sample size was 200 computerized tomography head axial section scans without any disease which might alter the anatomy of foramen, from picture archiving and communication system. Bilateral foraminal parameters were obtained with the help of computer-assisted software. Results: The mean length, breadth, distance from mid-sagittal plane, and size of FO in males were 7.75 ± 1.16, 3.98 ± 0.91, 21.40 ± 1.75, and 30.94 ± 8.79, and in females, measurements were 6.90 ± 0.78, 3.57 ± 1.04, 20.36 ± 1.62, and 24.86 ± 9.08, respectively. Septation was observed in 2% of cases and the most common shape observed was oval (84%). Totally 26% of accessory foramina were observed. Conclusion: Significant gender differences were seen in the morphometry in all the four parameters. A significant difference with age was seen only with distance of foramen from midsagittal plane. Variations in morphometry and shapes of the FO may affect clinical and diagnostic procedures.